Nghiên cứu tổng hợp một số dẫn xuất eugenol và khả năng ức chế ăn mòn kim loại của chúng - Hoan, Phạm Văn; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2014)
Four derivatives of eugenol, the ethereal oil extracted from Huong nhu essential oil (Clove oil), have been synthesized and characterized, essentially the chemical composition and molecular structure. The corrosion inhibition ability of these derivatives has been studied by using electrochemical potentiostatic technique (PS) in order to determine opened circuit potential, an important thermodynamic corrosion parameter. All four derivatives have manifested strong corrosion inhibition, from which eugenoxyacetic acid (M1), and 2-methoxy-4-(2-propenyl)phenoxyacetylhydrazine (M2) are the best inhibitors.